(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the effect of the acupuncture method to treat chronic sinusitis which is typed by traditional medicine. Subjects and methods: Clinical intervention study, comparison before and after treatment 50 patients diagnosed with chronic sinusitis according to the diagnostic criteria of the American Academy of Otolaryngology in 2007. Patients were implanted with Catgut suture into the acupoints: Phong Tri, Thai duong, Nghinh huong, Quyen lieu, Giap xa, Khuc tri, Hop coc, and Tuc tam ly. Follow-up and evaluation of results at 2 times: before treatment (D0) and after 15 days of treatment (D15). Results: The disease types according to traditional medicine are Lung deficiency and stagnation accounting for 40% and Spleen deficiency and dampness stagnation accounting for 60%. After 15 days of treatment, all symptoms according to the SNOT-22 scale had an average score that decreased compared to before treatment, the average score of SNOT-22 decreased by 13.16 ± 5.4 points (p < 0.05). Physical symptoms through endoscopic examination also improved: the average total score after treatment decreased by 1.06 ± 0.51 points compared to before treatment (p < 0.05). The total score of SNOT-22 of Lung deficiency and stagnation and Spleen deficiency and dampness stagnation according to traditional medicine both decreased by 16.80 ± 4.75 points and 10.73 ± 4.37 points, respectively (p < 0.05). The total physical symptom score according to the Lund - Kennedy scale of the Lung deficiency and stagnation and Spleen deficiency and dampness stagnation types decreased all compared to before treatment: the Lung deficiency and stagnation type decreased by 42.1%, the Spleen deficiency and dampness stagnation type decreased by 68.4% compared to before treatment (p < 0.05). The symptoms according to traditional medicine all decreased compared to before treatment (p < 0.05). Conclusion: The suture implantation is effective method in improving functional and physical symptoms in the treatment of chronic sinusitis and has equivalent effectiveness on the two types of Lung deficiency and stagnation and Spleen deficiency and dampness stagnation according to traditional medicine.